Studi Sistem Dispersi Padat Asam Mefenamat Menggunakan Polivinilpirolidon K-30 - Maria Dona Octavia; Erizal Zaini; Vina Oktavia (STIFARM Padang, 2015)
Mefenamic acid was categorized as Non-Steroidal Anti-Inflamatory Drugs (NSAIDs) which has useful as analgesic, anti inflammatory, and antypiretic effect but it has poor solubility in water. The aim of this study was to increase the dissolution rate of mefenamic acid in a solid dispersion system which made by solvent method. Solid dispersion and physical mixture prepared with ratio 1:1, 1:3, and 1:5. Solid dispersion was prepared by solvent method Preparation of solid dispersion mefenamat acid – PVP-K30 in formula 1:3 was increased of dissolution significantly. Characterization of Solid dispersion Mefenamic Acid with Polyvinylpyrrolidone used Scanning Electron Microscopy (SEM), X-Ray, Spectroscopy IR, Differentyal Thermal Analysis (DTA). The result of X-ray diffraction characterization the dissolution Mefenamic Acid-Polyvinylpyrrolidone in which the intensity is visible. The characterization with DTA showed a change in the peak of Mefenamic Acid where the endoterm, the characterization using infrared spectroscopy shows no functional group interaction between Mefenamic Acid and Polyvinylpyrrolidone.